Identifying the approaches used by audiologists to address the psychosocial needs of their adult clients. (1st February 2021) - Bennett, Rebecca J.; Barr, Caitlin; Montano, Joseph; Eikelboom, Robert H.; Saunders, Gabrielle H.; Pronk, Marieke; Preminger, Jill E.; Ferguson, Melanie; Weinstein, Barbara; Heffernan, Eithne; van Leeuwen, Lisette; Hickson, Louise; et al.
Abstract: Objective: To identify the approaches taken by audiologists to address their adult clients' psychosocial needs related to hearing loss. Design: A participatory mixed methods design. Participants generated statements describing the ways in which the psychosocial needs of their adult clients with hearing loss are addressed, and then grouped the statements into themes. Data were obtained using face-to-face and online structured questions. Concept mapping techniques were used to identify key concepts and to map each of the concepts relative to each other. Study sample: An international sample of 65 audiologists. Results: Ninety-three statements were generated and grouped into seven conceptual clusters: Client Empowerment; Use of Strategies and Training to Personalise the Rehabilitation Program; Facilitating Peer and Other Professional Support; Providing Emotional Support; Improving Social Engagement with Technology; Including Communication Partners; and Promoting Client Responsibility. Conclusions: Audiologists employ a wide range of approaches in their attempt to address the psychosocial needs associated with hearing loss experienced by their adult clients. The approaches described were mostly informal and provided in a non-standardised way. The majority of approaches described were not evidence-based, despite the availability of several options that are evidence-based, thus highlighting the implementation gap between research and clinical practice.